Methodological Guide for Professional Development of Nurses of the Surgical Emergency Units - Marlene Llanes Montero; Pedro Miguel Milián Vázquez; Lidia Vázquez Montero; Carlos Martín Álvarez; María de los Ángeles López Torres; Ana Margarita Quintero Alonso (Medisur)
Background: professional development is a priority in Cuban health policy, as a way to promote the quality care of patients. Objective: to design a methodological guide for the professional development of nurses working in Surgical Emergency Units. Methods: a descriptive study was conducted during 2009 and 2010 at the Gustavo Aldereguía Lima Hospital in Cienfuegos. A sample of 18 nurses of the Surgical Emergency Unit was selected for assessing their training needs. The guide was designed and subjected to expert judgment. Results: the insufficient professional preparation of nurses regarding the perioperative period was determined and their training needs were shown. The guide was designed according to the planning, implementation and evaluation of workshops to train the nursing staff. Specialists stated the quality of the proposal to help resolve the problems mentioned. Conclusions: implementation of the methodological guide for professional development of the nurses working in the Surgical Emergency Units should prepare them to improve care of patients.